Measurement of neutrino flux from neutrino-electron elastic scattering - Park J. (2016)
Muon-neutrino elastic scattering on electrons is an observable neutrino process whose cross section is precisely known. Consequently a measurement of this process in an accelerator-based νμ beam can improve the knowledge of the absolute neutrino flux impinging upon the detector; typically this knowledge is limited to ∼10% due to uncertainties in hadron production and focusing. We have isolated a sample of 135±17 neutrino-electron elastic scattering candidates in the segmented scintillator detector of MINERvA, after subtracting backgrounds and correcting for efficiency. We show how this sample can be used to reduce the total uncertainty on the NuMI νμ flux from 9% to 6%. Our measurement provides a flux constraint that is useful to other experiments using the NuMI beam, and this technique is applicable to future neutrino beams operating at multi-GeV energies. © 2016 American Physical Society.